2012
DOI: 10.3390/brainsci2040434
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Brain Changes Associated with Methamphetamine Abuse

Abstract: Methamphetamine (MA) is a potent psychostimulant drug whose abuse has become a global epidemic in recent years. Firstly, this review article briefly discusses the epidemiology and clinical pharmacology of methamphetamine dependence. Secondly, the article reviews relevant animal literature modeling methamphetamine dependence and discusses possible mechanisms of methamphetamine-induced neurotoxicity. Thirdly, it provides a critical review of functional and structural neuroimaging studies in human MA abusers; inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 196 publications
(530 reference statements)
2
21
0
Order By: Relevance
“…This raises the possibility that the integrity of frontal cortical brain networks implicated in the executive functions listed above might be compromised in methamphetamine-dependent patients. This concurs with evidence for metabolic, structural and functional anomalies in the middle frontal and DLPFC in chronic methamphetamine users Jan et al, 2012).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This raises the possibility that the integrity of frontal cortical brain networks implicated in the executive functions listed above might be compromised in methamphetamine-dependent patients. This concurs with evidence for metabolic, structural and functional anomalies in the middle frontal and DLPFC in chronic methamphetamine users Jan et al, 2012).…”
Section: Introductionsupporting
confidence: 89%
“…Striatal pathways project to brain regions implicated in top-down cognitive control, such as the dorsolateral prefrontal cortex (DLPFC) (Alexander et al, 1986). This concurs with evidence for metabolic, structural and functional anomalies in the middle frontal and DLPFC in chronic methamphetamine users Jan et al, 2012). This concurs with evidence for metabolic, structural and functional anomalies in the middle frontal and DLPFC in chronic methamphetamine users Jan et al, 2012).…”
Section: Introductionsupporting
confidence: 57%
“…Cadet et al, 2010; Jan et al, 2012a) has prompted evaluation of chemical markers of neuronal integrity and neuroinflammation with MRS in methamphetamine users. These studies have shown lower levels of n -acetyl-aspartate (NAA) metabolites and a lower ratio of NAA to creatine and phosphocreatine (Cr) metabolites – indicating poorer neuronal integrity and viability – among methamphetamine abusers relative to healthy controls in frontal brain regions, particularly the ACC (Ernst et al, 2000; Nordahl et al, 2002; Nordahl et al, 2005; Sailasuta et al, 2010; Sung et al, 2007).…”
Section: Molecular Imaging Of Methamphetamine Usersmentioning
confidence: 99%
“…There are increasing evidences that chronic methamphetamine use was associated with abnormalities in brain morphometry, function and metabolism (Jan et al 2012;London et al 2015;Salo and Fassbender 2012). However, whether these brain abnormalities can recover with abstinence remains unclear and longitudinal studies are needed to shed lights on it.…”
Section: Introductionmentioning
confidence: 99%